2016
DOI: 10.1111/raq.12144
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability vs. Quality in gilthead seabream (Sparus aurata L.) farming: are trade‐offs inevitable?

Abstract: European aquaculture industry should be at the forefront of sustainable development, providing healthy and safe food of the highest quality to the consumer, through an environmentally sound approach. The purpose of this review was to explore in what way the current drive for sustainability has affected what the consumer perceives as quality in fish, specifically in gilthead seabream, one of the most important farmed species in the Mediterranean. It focuses on nutritional aspects such as fish meal and fish oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 95 publications
0
37
0
Order By: Relevance
“…Alternative formulations are nowadays being directed to an ecofriendly approach (Matos et al, ) that targets a reduction of nutrient outputs to the environment. Nitrogen discharges to the environment result from both faecal losses, mostly related with low dietary protein digestibility, and from metabolic losses, resulting, for instance, from an imbalanced dietary amino acid profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative formulations are nowadays being directed to an ecofriendly approach (Matos et al, ) that targets a reduction of nutrient outputs to the environment. Nitrogen discharges to the environment result from both faecal losses, mostly related with low dietary protein digestibility, and from metabolic losses, resulting, for instance, from an imbalanced dietary amino acid profile.…”
Section: Discussionmentioning
confidence: 99%
“…At a short/medium term, this strategy places aquaculture in competition with biofuel and agricultural production for food (Olsen & Hasan, 2012), which is also expected to augment due to population increase. Furthermore, researchers and feed producers advert that a wider range of alternative ingredients to fishmeal are needed to fulfil the expected increase in aquaculture production (Matos, Dias, Dinis, & Silva, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The numerous studies examining the effect of replacing FM and FO with plant ingredients on many fish species have shown varying degrees of success (Nasopoulou & Zabetakis, ; Sales & Glencross, ; Sutili, Gatlin, Heinzmann, & Baldisserotto, ). This is particularly relevant for carnivorous fish species that have high FM and FO dietary requirements, such as Atlantic salmon, Salmo salar , and rainbow trout, Oncorhynchus mykiss (Hardy, ), as well as gilthead sea bream, Sparus aurata , (Sitjà‐Bobadilla et al, ) and European sea bass, Dicentrarchus labrax (hereafter sea bass) (Kaushik, Covès, Dutto, & Blanc, ), which have been driving marine aquaculture in the Mediterranean over the past decades (Kousoulaki, Sæther, Albrektsen, & Noble, ; Matos, Dias, Dinis, & Silva, ). While some studies have shown the successful replacement of FM and FO with plant‐based products in sea bream and sea bass feed, several problems have been identified, including reduced growth, feeding, and nutrient utilization (Montero, Robaina, Caballero, Ginés, & Izquierdo, ; Peres & Oliva‐Teles, ; Santigosa et al, ; Torrecillas et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The numerous studies examining the effect of replacing FM and FO with plant ingredients on many fish species have shown varying degrees of success (Nasopoulou & Zabetakis, 2012;Sales & Glencross, 2011;Sutili, Gatlin, Heinzmann, & Baldisserotto, 2017). This is particularly relevant for carnivorous fish species that have high FM and FO dietary requirements, such as Atlantic salmon, Salmo salar, and rainbow trout, Oncorhynchus mykiss (Hardy, 2010), as well as gilthead sea bream, Sparus aurata, (Sitjà-Bobadilla et al, 2005) and European sea bass, Dicentrarchus labrax (hereafter sea bass) (Kaushik, Covès, Dutto, & Blanc, 2004), which have been driving marine aquaculture in the Mediterranean over the past decades (Kousoulaki, Saether, Albrektsen, & Noble, 2015;Matos, Dias, Dinis, & Silva, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the obvious effects in fillet fatty acids, also the total volatile compounds and sensory properties, namely, the appearance, odour, flavour, and texture of fillet, can be affected [8][9][10][11][12][13][14]. In particular, in cases of sweet-water fish species, the recorded impacts included reduction of the total amount of aldehydes and alcohols concomitant to fillet n-3 fatty acids reduction, increase of n-6 derived aldehydes, and related sensory-perceived "off-flavour" for plant oil fed fish [9,10,15].…”
Section: Introductionmentioning
confidence: 99%